2010
DOI: 10.3354/meps08477
|View full text |Cite
|
Sign up to set email alerts
|

Strong enhancement of chlorophyll a concentration by a weak typhoon

Abstract: Recent studies demonstrate that chlorophyll a (chl a) concentrations in ocean surface waters can be significantly enhanced due to typhoons. The present study investigated chl a concentrations in the middle of the South China Sea (SCS) from 1997 to 2007. Only the Category 1 (minimal) Typhoon Hagibis (2007) had a notable effect on chl a concentrations. Typhoon Hagibis had a strong upwelling potential due to its location near the equator, and the forcing time of the typhoon (> 82 h) was much longer than the geost… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 28 publications
2
92
1
Order By: Relevance
“…All of these physical responses in the ocean can have a great impact on phytoplankton blooms (D'Asaro, 2003;Sun et al, 2010;, especially when the translational speed of the typhoon is relatively slow . The biophysical responses to this typhoon were investigated by who concluded that typhooninduced entrainment, vertical mixing and upwelling resulted in a significant enhancement of chlorophyll-a concentration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All of these physical responses in the ocean can have a great impact on phytoplankton blooms (D'Asaro, 2003;Sun et al, 2010;, especially when the translational speed of the typhoon is relatively slow . The biophysical responses to this typhoon were investigated by who concluded that typhooninduced entrainment, vertical mixing and upwelling resulted in a significant enhancement of chlorophyll-a concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Price's formula is approximately equivalent to the product of the potential Ekman pumping velocity and translation time and overestimates the real upwelling strength (see Eq. (5) in Sun et al (2010)). In comparison, Shay's formula, Eq.…”
Section: Upper Ocean Responses To Namtheunmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the distance between the cooling center and the typhoon track depend mainly on the typhoon's travelling speed [18]. Moreover, studies have suggested that the degree of typhoon-induced SSC depends not only on the intensity of the typhoon and its travelling speed, but also on the mixing layer depth [8,9] and the pre-existing eddies [19][20][21][22][23][24][25]. By analyzing four typical tropical cyclones in the South China Sea, Zhang et al concluded that the stronger the intensity of a tropical cyclones, the slower the movement speed, the shallower the mixed layer depth, and the greater the reduction in SST [24].…”
Section: Introductionmentioning
confidence: 99%